Gardnerella Exposures Alter Bladder Gene Expression and Augment Uropathogenic Escherichia coli Urinary Tract Infection in Mice - Gilbert, Nicole M.; O’Brien, Valerie P.; Waller, Chevaughn; Batourina, Ekatherina; Mendelsohn, Cathy Lee; Lewis, Amanda L. (Frontiers in Cellular and Infection Microbiology, 2022)
The anaerobic actinobacterium Gardnerella was first isolated from the bladder by suprapubic aspiration more than fifty years ago. Since then, Gardnerella has been increasingly recognized as a common and often abundant member of the female urobiome. Some studies even suggest that the presence of Gardnerella is associated with urological disorders in women. We recently reported that inoculation of Gardnerella into the bladders of mice results in urothelial exfoliation. Here we performed whole bladder RNA-seq in our mouse model to identify additional host pathways involved in responses to Gardnerella bladder exposure. The transcriptional response to Gardnerella reflected the urothelial turnover that is a consequence of exfoliation, and also involved activation of a variety of pathways involved in inflammation and immunity. Additional timed exposure experiments in mice provide further evidence of a potentially clinically relevant consequence, suggesting that bladder exposures to Gardnerella can increase susceptibility to subsequent UTI caused by uropathogenic Escherichia coli. Together these data provide a broader picture of the bladder response to Gardnerella and provide the groundwork for future studies examining the impact of Gardnerella on bladder health.